Management of OSN Extracurricular Activities in Enhancing Students’ Academic Achievement at Schools - Muhamad Nur Yasin; Khoirul Rahmadani; Rosyta Sofiyatun Munawaroh; Kusnul Khotimah; Saveena Meira Iskandar; Desyka Rizky Irmaningtyas (Al-Qalam Institue, 2026)
This study aims to analyze the management of the National Science Olympiad (OSN) extracurricular program in improving students’ academic achievement at SMAN 1 Jogorogo. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving the school principal, OSN program coordinator, OSN coaches, and participating students. The findings reveal that the management of the OSN extracurricular program is implemented systematically through the stages of planning, organizing, implementation, and evaluation. The transformation of OSN into a continuous extracurricular activity provides wider opportunities for students to receive long-term and structured coaching, which enhances their academic preparedness. Regular and intensive training strengthens students’ analytical skills, self-regulation, and achievement motivation. Nevertheless, several challenges remain, including unequal student interest across subject areas, limited facilities, and increasingly intense competition from other schools. Overall, the study concludes that effective management of the OSN extracurricular program contributes significantly to improving students’ academic achievement and offers a relevant model for the development of competition-based extracurricular programs in secondary schools